2007
DOI: 10.1007/s00223-007-9075-4
|View full text |Cite
|
Sign up to set email alerts
|

Morphogenetic Activity of Silica and Bio-silica on the Expression of Genes Controlling Biomineralization Using SaOS-2 Cells

Abstract: In a previous study (Schröder et al., J Biomed Mater Res B Appl Biomater 75:387-392, 2005) we demonstrated that human SaOS-2 cells, when cultivated on bio-silica matrices, respond with an increased hydroxyapatite deposition. In the present contribution we investigate if silica-based components (Na-silicate, tetraethyl orthosilicate [TEOS], silica-nanoparticles) (1) change the extent of biomineralization in vitro (SaOS-2 cells) and (2) cause an alteration of the expression of the genes amelogenin, ameloblastin,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 53 publications
(32 citation statements)
references
References 70 publications
0
32
0
Order By: Relevance
“…Known since the seventies is the fact that silica is one inorganic component that is required during the early steps in bone formation [61,62]. However, recently the silicate metabolism has been investigated more intensively both in vivo [63] and in vitro [38,45,48]. The recent finding that biosilica, the polymer of silica, acts in vitro as an inducer of OPG while leaving the steady-state expression of RANKL unaffected suggests that the polymer is a new factor inhibiting osteoclast maturation [38] (see the scheme in Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Known since the seventies is the fact that silica is one inorganic component that is required during the early steps in bone formation [61,62]. However, recently the silicate metabolism has been investigated more intensively both in vivo [63] and in vitro [38,45,48]. The recent finding that biosilica, the polymer of silica, acts in vitro as an inducer of OPG while leaving the steady-state expression of RANKL unaffected suggests that the polymer is a new factor inhibiting osteoclast maturation [38] (see the scheme in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…SaOS-2 cells (human osteogenic sarcoma cells [43]) were cultured in McCoy's medium (containing 1 mM CaCl 2 ), with 5% heat-inactivated fetal calf serum (FCS), 2 mM L-glutamine and gentamicin (50 lg ml -1 ) in 6-well plates (surface area 9.46 cm 2 ; Orange Scientifique, Braine-l'Alleud; Belgium) at a density of 5 Â 10 3 cells cm -2 in a humidified incubator at 37°C and 5% CO 2 , as described previously [44,45].…”
Section: Cells and Incubation Conditionsmentioning
confidence: 99%
“…AMBN is present in the secretory stage of enamel formation, as demonstrated by immunostaining of ameloblastin (21). It has recently been revealed that AMBN is also expressed in osteoblasts during craniofacial skeletal development and in an osteosarcoma cell line, SaOS-2, cultivated on biosilica matrices (19,25). However, the function of AMBN in osteoblasts is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…They also support the safety of nanosilicas that are used in the production of highly functional materials for oral care fields [1,20]. We believe that applications of nanosilica will extend to these new fields in the near future following further careful safety study.…”
Section: Resultsmentioning
confidence: 64%